Magnificat – maryjny „toast na cześć Boga” - NADBRZEŻNY, Antoni (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The Canticle of Mary, also called the Magnificat, is counted among the «pearls of Biblical literature.» It expresses the joy of Mary over the glory of the works of God done for herself as well as for the world and its history. An exegetical analysis of the Magnificat reveals that the joy of Mary is not merely a manifestation of her momentary enthusiasm; neither does it express a spontaneous and uncontrolled explosion of optimism. On the contrary, the joy of Mary is due to much deeper sources. As far as the personal history of Mary is concerned, they comprise: the fact that God has chosen a simple and unknown girl to become the Mother of the Son of God, her experience of the unconditional and absolutely gratuitous grace of redemption, manifested in the mystery of her immaculate conception, the gift of the Holy Spirit she received in the Annunciation, her being put in the center of the history of salvation, and her faithful companionship with Christ throughout his work of redemption. From the perspective of universal history, the sources of the joy of Mary include: God’s mercy and charity, his loyalty to the promises he has made, his active presence in the history of Israel and in the history of the entire humanity, the fact that he radically champions the poor and the oppressed as well as restores social justice. To the Church, Mary constitutes a paragon of joyous fulfillment of the salvific mission in the world and she is a prophetic sign of eschatological joy. Translated by Dorota Chabrajska